Evaluating Internal Audit Quality (Evidence From Iraq) - Abdllah Abdulnabi Waheed; A.M.D. Maytham Bader Bawie Al-Sfan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Abstract: This research paper aims to evaluate the quality level of internal auditing in the banking sector in Iraq, using a set of data obtained by the researcher by submitting the checklist for the period (2023-2024), which contains four axes related to attribute standards and seven axes related to performance standards to the sample banks. The research, and based on the answers of those banks, the researcher used the Excel program to sort the data to conduct statistical analysis on it. The results revealed by these statistical analyzes were reached regarding the level of application of professional practice standards for the internal audit function in the Iraqi banking sector. The percentage of application of attribute standards indicated (90 %) with an average of (4.5%) as a very high percentage of application. As for the performance standards, it achieved a percentage of (88%) with an average of (4.4%) also as a good percentage in application. These percentages explain that the application of standards in the banking sectors improves the quality of internal auditing, which reflects positively. At the level of banking services provided to customers, these results constitute an incentive to measure further research, analysis, and factors that helped improve the quality of internal auditing.